2011
DOI: 10.4149/gpb_2011_si1_36
|View full text |Cite
|
Sign up to set email alerts
|

Functional characteristics of ram cooling-stored spermatozoa under the influence of epidermal growth factor

Abstract: Abstract. The aim of the study was to examine the effects of epidermal growth factor (EGF) on ram sperm traits following hypothermic storage. Fresh ram ejaculates were diluted in Triladyl extender, pooled and divided into groups according to EGF doses added (0, 100, 200 or 400 ng/ml). Following 72-96 h storage at 4°C, the spermatozoa were stained for a plasma membrane integrity (PNA-FITC), membrane phosphatidylserine (PS) translocation (annexin V-Fluos) and apoptosis (Yo-Pro-1), and analyzed by fluorescent mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
0
15
1
Order By: Relevance
“…Former studies localized EGF receptors at higher extent in the acrosome region than to the post-acrosome and the flagellum [7]. Although no former studies verified the effect of EGF on frozen semen characteristics, fresh ram semen stored with EGF at 4 ℃ showed an enhanced motility, viability and membrane integrity [26]. EGF increased ram spermatozoa motility at all doses tested, especially when EGF was added to the spermatozoa after 2-day of storage.…”
Section: Discussionmentioning
confidence: 99%
“…Former studies localized EGF receptors at higher extent in the acrosome region than to the post-acrosome and the flagellum [7]. Although no former studies verified the effect of EGF on frozen semen characteristics, fresh ram semen stored with EGF at 4 ℃ showed an enhanced motility, viability and membrane integrity [26]. EGF increased ram spermatozoa motility at all doses tested, especially when EGF was added to the spermatozoa after 2-day of storage.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Maxwell et al (1995) reported no effect of caffeine on the acrosome integrity of frozenthawed ram spermatozoa. For successful fertilization, high incidence of sperm with intact membrane is necessary, because intact plasma membrane is an essential requirement for sperm cell function (Makarevich et al 2011). Spermatozoa with damaged or inactive membranes have limited viability and fertilization potential (Correa and Zavos 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The sperm with PS translocation exhibited green fluorescence and was regarded as sperm with membrane destabilization. Presence of annexin V-positivity in sperm was localized on the acrosomal part of the sperm head, post-acrosomal segment, equatorial segment and on sperm membrane along the entire head (Makarevich et al 2011). …”
Section: Analysis Of Sperm Viabilitymentioning
confidence: 99%
See 2 more Smart Citations